Consistency Of Corporate Criminal Law Enforcement Against Money Laundering Offenses - Faruq Rozy; Yasmirah Mandasari Saragih; Abdi Ridho; Nurul Aini; Berlian Evi Yenni Pakpahan (Pusat Riset dan Inovasi Nasional, 2025)
The phenomenon of money laundering crimes committed by corporations shows an increasingly complex and organized trend. Law enforcement against corporate offenders often faces obstacles in terms of regulations and weaknesses of the criminal justice system. In this context, the consistency of law enforcement becomes crucial to ensure legal certainty and justice. This research aims to examine the consistency of corporate criminal law enforcement in money laundering cases and identify relevant challenges and solutions. The research method used is normative juridical with statutory approaches and case studies. The results of the study show that although there is an adequate legal umbrella, implementation in the field is still inconsistent, both in terms of proving corporate guilt and in imposing sanctions. It is necessary to harmonize regulations and increase the capacity of law enforcers to realize an effective corporate criminal law system in tackling money laundering crimes.